AGRIBISNIS SAGU UBI KAYU DI KELURAHAN JAYA, KECAMATAN TIDORE UTARA, TIDORE KEPULAUAN - FATMAWATI KADDAS (Fakultas Pertanian Universitas Yudharta Pasuruan, 2017)
Cassava in Indonesia has been developed since long time ago considering this plant has been a staple of the Indonesian population as well as rice and corn. In Jaya village, Tidore islands, predominantly they processing cassave into refined products of cassava starch commonly known as sago kasbi, this activity has been occupied for generations. This study aims to determine the production and marketing of cassava starch, knowing the cost and revenue, and determine the level of cassava starch feasibility. Research was conducted during the months of April to September 2012, located in the Jaya Village, North Tidore District, Tidore islands. The sampling method used in this study was purposive simple method by the number of respondents who were taken by 20% which is 27 respondents of 134 person who seek cassava starch. The research results obtained is the analysis of the average cost respondent worth Rp. 478,040.93, while the revenue earned by the respondent amounted to Rp. 333,070.19, while the calculation of the R / C ratio average at 1.72 and π / C Ratio at 61.76, with the income of the average respondent of cassava starch processing, the business is worth to be developed. So, there is a need for the development of cassava starch product diversity and product storage container so that production can be routinely obtained thus revenue can also be increased.